A Review of the Potential Use of Entomopathogenic Nematodes to Control Above-Ground Insect Pests in South Africa - Platt, T.; Stokwe, N.F.; Malan, A.P. (South African Journal of Enology and Viticulture, 2020)
Entomopathogenic nematodes (EPNs), of the families Steinernema and Heterorhabditis, are insect parasites that have been successfully used as biological control agents of soil-based insect pests on the North American and European continents. The success of nematodes as biological control agents of the soil stages of pest insects has led to research into their use for control of above-ground insect pests. Laboratorybased studies have shown exceptionally good control, in most cases, against such pests as mealybugs, codling moth and leaf miners. As the life stages of the above-ground insect pests have not co-evolved together with those of EPNs, they are, generally, more susceptible than the soil-based life stages. However, EPNs are susceptible to desiccation and vulnerable to UV radiation, so that ensuring their survival beyond soil environments is problematic. The impetus to avoid environmental stressors can cause EPNs to seek sheltered, cryptic habitats on foliage, where their target insect pest (such as mealybugs) may be found. The current paper provides an overview of information on the application of EPNs as a biocontrol agent for the control of insect pests above ground and on foliage, with particular reference to research done in South Africa.